Globba praetermissa (Zingiberaceae), a new species of G. sect. Globba from Yunnan, China - Jin, Jia Yi; Wang, Yi Hui; Xia, Nian He; Bai, Lin (Phytotaxa, 2023)
China represents the northern distribution margin of the genus Globba, with only eight species recorded previously. However, the identity of some of the species remains problematic. Globba barthei was recorded as occurring in Guangxi, Guizhou and Yunnan provinces by some authors, although the name had been regarded as a synonym of G. marantina by others. Based on specimen examination and field study, we confirm that some of the specimens that were previously identified as G. barthei indeed belong to G. marantina, while others represent a new species, which is described here as G. praetermissa. We have confirmed that G. barthei is conspecific with G. marantina and the latter name should be adopted. Furthermore, this species is newly reported in Hainan province. Globba praetermissa, which is known from southern Yunnan Province, is most similar to G. purpurascens, a species distributed in northern Thailand and northern Laos, in having lax, pendent inflorescence, densely ciliate bracts and lateral staminodes being nearly equal in length to the lateral corolla lobes. However G. praetermissa differs by having green upper leaf sheaths, ovate or elliptic and larger laminae, ovate, pale green and larger bracts, pedicels fully enclosed by bracteoles, longer calyx, and six appendages including a smaller pair between the two larger pairs. Furthermore, no fruits of G. praetermissa were seen in herbarium specimens or in the field and according to previous studies, the species is probably triploid with 2n=48, while G. purpurascens is a diploid with 2n=36, which produce fruits. A tabulated comparison of G. praetermissa, G. marantina and G. purpurascens as well as color plates of the first two species are provided.